2002
DOI: 10.1073/pnas.052520799
|View full text |Cite
|
Sign up to set email alerts
|

Proton shuttle in green fluorescent protein studied by dynamic simulations

Abstract: As a direct simulation of a multistep proton transfer reaction involving protein residues, the proton relay shuttle between A and I forms of green fluorescent protein (GFP) is simulated in atomic detail by using a special molecular dynamics simulation technique. Electronic excitation of neutral chromophore in wild-type GFP is generally followed by excited-state proton transfer to a nearby glutamic acid residue via a water molecule and a serine residue. Here we show that the second and third transfer steps occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
136
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 31 publications
10
136
0
1
Order By: Relevance
“…Helms et al 40 observed that, although in their starting structure Arg168 sticks out to the solution, during the 318-ps simulations it folds back to the protein surface to form a hydrogen bond with Ser147. The anionic chromophore shows additional hydrogen-bonding to His148 and Thr203 but not to Ser205, which instead is hydrogen bonded to W 22 . The increased hydrogenbonding pattern for the anionic chromophore can additionally explain the larger rotational barrier for 2 rotation observed in the ONIOM model(II).…”
Section: Protein Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Helms et al 40 observed that, although in their starting structure Arg168 sticks out to the solution, during the 318-ps simulations it folds back to the protein surface to form a hydrogen bond with Ser147. The anionic chromophore shows additional hydrogen-bonding to His148 and Thr203 but not to Ser205, which instead is hydrogen bonded to W 22 . The increased hydrogenbonding pattern for the anionic chromophore can additionally explain the larger rotational barrier for 2 rotation observed in the ONIOM model(II).…”
Section: Protein Structurementioning
confidence: 99%
“…GFP exhibits strong two-photon absorption (TPA) and therefore has great potential for a wide range of applications, ranging from three-dimensional fluorescence imaging, optical data storage to microfabrication. 18 -21 Previous QM/MM studies have addressed the excited states of the chromophore, [22][23][24][25] but the understanding of the spectra of the protein is far from complete. Although time-dependent density functional theory (TDDFT) calculations with the initial structure derived using a QM/MM (specifically, DFT/ AM1) approach have been recently reported, 23 the nonlinear optical response has not been examined, and accurate calculations of the TPA cross section with an understanding of the structure and energetics in the excited state are still required.…”
Section: Introductionmentioning
confidence: 99%
“…5) 17 but similar to that of an alcohol (Δ = [30][31][32][33][34][35][36][37][38][39][40]. 18,19 On the other hand, biological processes often take place based on proton relay along a hydrogen (H)-bonded chain, [1][2][3][4][20][21][22][23][24] and the dynamics of biological proton relay is determined by the size, the structure, and the motion of a water cluster which is the prime agent in most of biological systems. 3,[13][14][15][24][25][26] Thus, for better understanding of cellular dynamics, it is necessary to investigate the properties of a biologically relevant water nanopool as a biomimetic system of water confined in a cell membrane.…”
Section: -16mentioning
confidence: 99%
“…
Water plays a crucial role in many principal biological phenomena such as enzymatic catalysis and proton pumping through a membrane protein channel.1-4 Moreover, in biological systems, water is usually contained in a small pocket of a membrane, 5-8 and such confined water, which is generally called a water nanopool, [8][9][10] shows peculiar properties differing considerably from the properties of bulk water.
8-16The confinement effect and the enclosing interfacial surfaces of waterpools are the main factors to determine the properties, such as polarity, viscosity, and H-bonding ability, of water nanopools.5-13 For example, the dielectric constant of a water nanopool has been reported to be much lower than that of bulk water (Δ = 78.5)17 but similar to that of an alcohol (Δ = 30-40).18,19 On the other hand, biological processes often take place based on proton relay along a hydrogen (H)-bonded chain, [1][2][3][4][20][21][22][23][24] and the dynamics of biological proton relay is determined by the size, the structure, and the motion of a water cluster which is the prime agent in most of biological systems. 3,[13][14][15][24][25][26] Thus, for better understanding of cellular dynamics, it is necessary to investigate the properties of a biologically relevant water nanopool as a biomimetic system of water confined in a cell membrane.
…”
mentioning
confidence: 99%
“…Die Transferwahrscheinlichkeiten hĂ€ngen vom momentanen Donor-AkzeptorAbstand (R DA ) und vom Energieunterschied zwischen den beiden Minima an Donor und Akzeptor (E 12 ) ab. Diese Methode wurde erfolgreich eingesetzt, um den Protonenshuttle im grĂŒn fluoreszierenden Protein zu untersuchen [40] und um den Mechanismus zu verstehen, der Aquaporin undurchlĂ€ssig fĂŒr Protonen macht. [41] Hier stellen wir die Anwendung von Q-HOP-MD auf die Berechnung des expliziten Protonierungsgleichgewichts der gelösten EssigsĂ€ure auf einer Zeitskala von 50 ns bei sinnvollen pH-Bedingungen (pH 1) vor.…”
unclassified